The medico‐legal autopsy: medicine, expertise, and death investigation - IMOGEN JONES (Journal of Law and Society, 2026)
Abstract This article sheds important new light on the hybrid space between medicine and law in which medico‐legal autopsies are situated. By examining original empirical data obtained during interviews with pathologists, I reveal a web of authority claims both within the profession and in its relationship to law. Drawing on the sociology of medicine, I note the importance of expert status to both the pathologist's identity and their contribution to law. This is constituted via a combination of trained technical skills and tacit knowledge. However, I note the ways in which these pathologists framed their conclusions as ‘opinion’. This, I argue, both reflects the ambiguity inherent in clinical judgement and is a device to limit credibility‐damaging challenges, especially during legal adjudications. It may therefore be that a gap exists between law's desire for facts and the contribution that these professionals can, and are willing, to contribute towards achieving that end.